Understanding seismic path biases and magmatic activity at Mount St Helens volcano before its 2004 eruption. Issue 1 (1st April 2020) - Gabrielli, S; De Siena, L; Napolitano, F; Del Pezzo, E
SUMMARY: In volcanoes, topography, shallow heterogeneity and even shallow morphology can substantially modify seismic coda signals. Coda waves are an essential tool to monitor eruption dynamics and model volcanic structures jointly and independently from velocity anomalies: it is thus fundamental to test their spatial sensitivity to seismic path effects. Here, we apply the Multiple Lapse Time Window Analysis (MLTWA) to measure the relative importance of scattering attenuation vs absorption at Mount St Helens volcano before its 2004 eruption. The results show the characteristic dominance of scattering attenuation in volcanoes at lower frequencies (3–6 Hz), while absorption is the primary attenuation mechanism at 12 and 18 Hz. Scattering attenuation is similar but seismic absorption is one order of magnitude lower than at open-conduit volcanoes, like Etna and Kilauea, a typical behaviour of a (relatively) cool magmatic plumbing system. Still, the seismic albedo (measuring the ratio between seismic energy emitted and received from the area) is anomalously high (0.95) at 3 Hz. A radiative-transfer forward model of far- and near-field envelopes confirms this is due to strong near-receiver scattering enhancing anomalous phases in the intermediate and late coda across the 1980 debris avalanche and central crater. Only above this frequency and in the far-field diffusion onsets at late lapse times. The scattering and absorption parameters derived from MLTWA are used as inputs to construct 2-D frequency-dependent bulk sensitivity kernels for the S -wave coda in the multiple-scattering (using the Energy Transport Equations—ETE) and diffusive (AD, independent of MLTWA results) regimes. At 12 Hz, high coda-attenuation anomalies characterize the eastern side of the volcano using both kernels, in spatial correlation with low-velocity anomalies from literature. At 3 Hz, the anomalous albedo, the forward modelling, and the results of the tomographic imaging confirm that shallow heterogeneity beneath the extended 1980 debris-avalanche and crater enhance anomalous intermediate and late coda phases, mapping shallow geological contrasts. We remark the effect this may have on coda-dependent source inversion and tomography, currently used across the world to image and monitor volcanoes. At Mount St Helens, higher frequencies and deep borehole data are necessary to reconstruct deep volcanic structures with coda waves.